Group Differences in Individual and Organizational Capabilities and Operational Performance in Implementing DX: Focusing on Nepalese SMEs - Marasini, Durga Prasad; Lee, DonHee; Joung, HyunSuk (Global business and finance review, 2023)
Purpose: The purpose of this study is to examine differences between excellent and following groups based on individual and organizational capabilities and operational performance, focusing on Nepalese SMEs. Design/methodology/approach: The proposed research model and a set of hypotheses were developed and tested using T-test analysis based on data collected from 154 (70.32%) responses in Nepal. Findings: From the T-test results showed a significant mean difference between excellent and following groups on change acceptance and technology acquisition on individual capabilities. In addition, the T-test results showed a significant mean difference between excellent and following groups on organizational infrastructure and organizational support, and operational performance showed the or a difference between the two groups. Research limitations/implications: The limitations of this study are the sample size and target respondents. The results of this study suggested practical insights for DX implementation for SMEs. Originality/value: The value of this study will be used as basic guidelines not only for companies that want to implement DX effectively but also for organizations that consider implementing DX.